PROTOTYPE DESIGN SYSTEM WITH LIFT PENDITEKSI IBM PC COMPUTER-BASED SMOKE - Freddy Susanto; Drs. Linga Hermanto, MMSi Drs. Linga Hermanto, MMSi (Jurnal Sistem Komputer, 2002)
In the development of transportation in the present, not just transportationtransportation vertical, but horizontal transport dibituhkan is to climb high-rises.Because it used a tool called an elevator.As transportasu vertically, the safety factor for horizontal transport is also veryimportant. Therefore one of the security tools that should be there is a smoke sensorin the elevator.That is a tool that can detect the smoke inside the elevator. Why use smoke sensors,because sensors can detect the smoke particles are small and a bit of smoke. So as todetect a larger smoke coming from fires can be detected properly.